Development of novel crystal scintillators for lunar surface science. (November 2022) - Vuong, Phan Quoc; Quang, Nguyen Duy; Kim, HongJoo; Lee, J.Y.; Kang, S.C.; Nam, Uk-Won; Park, Won-Kee; Sohn, Jongdae; Choi, Young-Jun; Youn, Sukwon; Ye, Sung-Joon; Kim, Sunghwan
Abstract: The development of novel crystal scintillators for a lunar landed mission near future is reported. On that mission, we aim to assess the radiation dose, biological effect, water, and other resources on the lunar surface. To accomplish this, a Lunar Vehicle Radiation Dosimeter (LVRAD) made up of several radiation detectors has been proposed. New scintillation crystals are being developed for neutron and gamma measurements. Stilbene and undoped LaCl3 crystal were selected for fast neutron/gamma spectrometers. The mutual combination of organic and inorganic detectors benefits from direct fast neutron detection via 35 Cl(n, p) 35 S reaction as well as the good gamma resolution of LaCl3 and the high detection efficiency of stilbene. LaCl3 crystals with the diameter of 38.1 mm were grown by a homemade modified Bridgman furnace. For epithermal neutron spectrometer, 6 LiI:Ag crystal was selected due to its pulse shape discrimination capability and highest detection efficiency in terms of size for both thermal and epithermal neutron among scintillation materials. Enrich 6 LiI was purified using the zone-refining technique. The crystal was then grown by the same Bridgman furnace. Highlights: Novel scintillators are developed for lunar surface science. Large crystals were grown using a homemade Bridgman furnace. Pure LaCl3 can separate gamma, alpha, and photon. 6 LiI:Ag is a sensitive thermal neutron sensor with Pulse shape discrimination.